Assessment of Esophageal High-Resolution Impedance Manometry in Patients with Nonobstructive Dysphagia - Zhaoyu Liu; Jiazhi Liao; Dean Tian; Mei Liu; Zili Dan; Qin Yu (Gastroenterology Research and Practice)
Background. High-resolution impedance manometry (HRIM) can calculate the bolus motion parameters and the ratio of complete esophageal transit besides the conventional esophageal dynamic parameters; therefore, we could better manage the patients with nonobstructive dysphagia (NOD) clinically. Aim. To analyze the HRIM parameter results of NOD patients and evaluate the characteristics of their esophageal motility and transit function. Methods. In total, 58 NOD patients were assessed and the clinical diagnoses were determined. HRIM was performed, and both conventional high-resolution manometry and esophageal transit parameters were analyzed. Results. In 58 NOD patients, 28 patients had achalasia, 3 esophagogastric junction outflow obstruction, and 20 nonspecific esophageal motility disorders, and 7 were normal. Impedance results demonstrated that all the patients with achalasia exhibited incomplete esophageal transit (ICET), three patients with esophagogastric junction outflow obstruction showed ICET, and the average bolus transit time (BTT) was 6.6 ± 1.2 sec. In 20 nonspecific esophageal motility disorders, 13 patients with gastroenterologly reflux disease (GERD) presented ineffective esophageal motility and fragmented peristalsis, and 65.0% swallows had exhibited ICET. However, 49.1% swallows of 7 nonspecific esophageal motility disorder patients with non-GERD had exhibited ICET. The average BTT in 13 GERD patients was longer than that in the non-GERD patients (8.1 ± 1.1 sec versus 5.5 ± 0.3 sec, P<0.05). And in the seven patients with normal esophagus function, 3.5% swallows showed ICET and BTT was 5.6 ± 0.3 sec. Conclusion. Achalasia was the most common esophageal dysmotility in NOD patients, followed by nonspecific esophageal motility disorders. The clinical diagnoses of NOD were mostly achalasia and GERD. Impedance assessments showed that all achalasia cases exhibited ICET, and other esophageal motility abnormalities that represented ICET were associated with contraction break and ineffective swallow. Compared to non-GERD patients, BTT was significantly prolonged in patients with GERD.